The effect of COVID-19 pandemic and wearing face masks on ophthalmology practice: What is known so far? A narrative review - Abu-Ismail, Luai; Al-Shami, Khayry; Al-Shami, Manar; Nashwan, Abdulqadir J. (Frontiers in Medicine, 2022)
Face masks, along with other preventive measures, can help slow the spread of COVID-19. Despite the positive effect of the mask in combating the virus, it has some negative effects on the human body that must be followed up on and reduced. In this study, we discuss the impact of wearing face masks on the eye and the common issues associated with using them. The literature search was conducted using electronic databases such as PubMed and Google Scholar. Only articles published in English were included. A total of 39 relevant articles were deemed eligible. After the duplicate articles were removed, the titles and abstracts of 20 papers underwent full-text screening. The review comprised both prospective and retrospective investigations, case reports, and a series of reporting ocular symptoms following the use of face masks. The COVID-19 pandemic affected ophthalmology practices in managing patients. New factors must be considered, especially when dealing with anti-VEGF injections, such as the risk of endophthalmitis, tests and symptoms of patients with glaucoma, and the emerging symptoms associated with the COVID-19 vaccination. The use of face masks and breathing aids seemed to influence the tear film.